Examination of risk factors of injuries between genders in beach handball - Hatzimanouil, D.; Zapartidis, I.; Terzidis, I.; Papasoulis, E.; Chronopoulou, C.; Makri, A. (Journal of Physical Education and Sports Management, 2018)
The aim of this study is to examine the injuries between genders. The study was contacted on 61 female and 60 male beach handball players that were participating in the EBT finals in 2016. These players completed a questionnaire which included information on personal characteristics, on prophylaxis and on characteristics of injuries. Incidence rate for men and women during games and trainings was 8.04 / 1000 hours, and 3.06 / 1000 hours and 7.9 / 1000 hours, and 2.75 / 1000 hours, respectively. The majority of injuries were very serious. The most common types of injuries were sprains and muscle strains for male inlower limbs (knee, ankle) and sprains in upper limbs (shoulder, elbow) for female. Contact injuries were more common than non-contact injuries for both genders. The chi-square test found that there is statistical significant difference between the gender and the place where an injury occurred (p=.045). Kendall`s tau-b test found that there is statistical significant correlation between the variable use of technical training and incidence of injuries in men (p=.046). Conclusively in this sport although the incidence is small, the severity, in many cases is very serious. Sometimes there is a difference in risk factors between genders.